Aspectos ecológicos de carrapatos (Acari: Ixodidae) no Parque Nacional do Iguaçu, Paraná, Brasil - Suzin, Adriane (2018)
The growing interest in studying tick ecology (Acari: Ixodidae) has been associated with ticks important role as hosts, vectors and amplifiers of a wide variety of microorganisms. The study of the epidemiological role of these organisms associated with their population and temporal dynamics is important to predict the risk of diseases transmission. In this study, ecological and behavioral aspects of free-living ticks and their interaction with hosts (birds, small non-flying mammals and humans) were studied in the Iguaçu National Park (INP), the largest preserved remnant of the Atlantic rainforest of South Brazil. Sampling of free-living ticks occurred seasonally (winter, spring, summer and fall) for two years, while sampling of birds and small non-flying mammals occurred in two seasons (one in winter and one in summer). In addition, human ticks were collected throughout the study period. In total, six species of ticks were collected: free-living Amblyomma brasiliense, A. coelebs, A. incisum, Haemaphysalys juxtakochi, A. ovale, and Ixodes aragaoi. Larvae were collected mostly between summer and fall; the number of nymphs was higher in winter than in spring and summer. Adults were collected more in winter and spring than in summer. All species presented questing behavior in the vegetation, with the highest numbers observed for A. brasiliense and A. incisum. Nymphs questes for hosts lower than adults, and larvae in height statistically equal to adults and nymphs. The composition of the tick community between two sites was not the same, and I. aragaoi was exclusively collected in INP Céu Azul county, while A. coelebs was mostly collected in the Foz do Iguaçu county. Globally, the flaging proved to be more efficient for collecting larvae and nymphs while the visual search for adult collection. Regarding host interactions, A. longirostre was collected exclusively in passerines. Small non-flying mammals did not exhibit parasitism. Humans were parasite by all species of the genus Amblyomma collected in free life, but mainly by A. coelebs. Our results point to a temporal pattern of the tick community, with a possible annual life cycle for most species and behavioral questing in the vegetation, probably related to host height. Given the difference in specimen composition among sites, additional studies related to the microscale population distribution could help to clarify aspects related to the spatial distribution of ticks. Similarly, samplings of birds and small mammals at larger temporal and spatial scales associated with serological and molecular investigations could confirm or reveal patterns of infestation and infection not verified here. Moreover, the temporal patterns of infestation in humans provided by this study may be valuable in reducing the risk of bites. Finally, additional ecoepidemiological investigations would be important for understanding the parasite-host relationships and their dynamics with the environment.